Migration and the Distributive Trades - Gillespie, Sarah C.; Rothschild, K. W. (Review of Economic Studies, 1945)
Sarah C. Gillespie, K. W. Rothschild; Migration and the Distributive Trades, The Review of Economic Studies, Volume 13, Issue 2, 1 January 1945, Pages 81–8